"x^2y^{\\prime \\prime}-xy^{\\prime}+17y=0" , "y_1=x\\sin(4\\ln x)"
Standard form of this equation is "y^{\\prime \\prime}-\\frac{1}{x}y^{\\prime}+\\frac{17}{x^2}y=0" .
For equation "y^{\\prime \\prime}+P(x)y^{\\prime}+Q(x)y=0" we have formula of second solution:
"y_2(x)=y_1(x)\\int \\frac{e^{-\\int P(x)dx}}{y^2_1(x)}dx" .
We have that "P(x)=-\\frac{1}{x}," "\\ \\ e^{ -\\int P(x)dx}=e^{\\int \\frac{1}{x}dx }=e^{\\ln x}=x" .
"y_2(x)=x\\sin(4\\ln x)\\int \\frac{1}{x\\sin ^2{(4\\ln x})}dx"
"\\int \\frac{1}{x\\sin ^2(4\\ln x)}dx =\\big[\\ \\ u=4\\ln x, \\ du=\\frac{4}{x}dx \\ \\ \\big]=\\frac{1}{4}\\int \\frac{1}{\\sin ^2 u}du=-\\frac{\\cot u}{4}+C=\u2014\\frac{\\cot (4\\ln x)}{4}+C"
"y_2(x)=-\\frac{1}{4}x\\sin (4\\ln x)\\cot (4\\ln x).=-\\frac{1}{4}x\\cos(4\\ln x)"
Answer: "y_2(x)= -\\frac{1}{4}x\\cos(4\\ln x)."
Comments
Leave a comment